Uniformity, sensitivity, linearity, and hot region image analysis by employing unconventional filter technique (Cu 0.125mm and AI 0.2mm) with Tc-99m inSPECT imaging - Vee, Fong Shu (2004)
In SPECT imaging, the presence of the scattered events in projection data affects the overall quality of the image as well as the quantification of the radioactivity distribution. In this study, material filter method has been employed in the attempt of reducing the influence of scatter events in the measured counts. Such a filter decreases the relative contribution of scattered gammas by preferentially removing them before they can reach the surface of the detector of the gamma camera. The material filters used are copper (Cu) sheet 0.125mm thick and aluminium (AI) sheet 0.2mm thick. Filters are separately mounted on the face of a gamma camera (GCA-901 A/HG) with either low energy general purpose (LEGP) or low energy high resolution (LEHR) collimators. SPECT images of the insert simulating 'hot' lesions in cold background, linearity and the uniform section of the Carlson phantom loaded with Tc-99m are obtained without and with material filter. The performance of the tomographic system is explored via the uniformity, sensitivity and linearity measurements, as well as the image lesi9n (hot) contrast, signal-to-noise ratio, standard deviation and percent root mean square noise (PRMSN). From the results, material filtered data shows an improvement in all tested parameters at the cost of system sensitivity.